The multilayered cuticle underlying structural coloration in red algae shares features with the metazoan extracellular matrix - Glenn Philippe; Olivier Godfroy; Frederic Beisson; Ambre Gautier; Diane Jouanneau; Sophie Le Panse; Emmanuelle Com; Ludovic Delage; Mirjam Czjzek; Elizabeth Ficko-Blean; Jonas Collén (Proceedings of the National Academy of Sciences, 2026)
Structural coloration, a physical phenomenon observed in many living organisms, may arise from the interference of light with highly organized surface nanostructures. In some seaweeds, these nanostructures consist of cuticular lamellae in the outer part of the extracellular matrix (ECM) of the epidermis. However, the chemical composition of seaweed cuticles is poorly understood and the molecular components of lamellae remain unidentified. Here, we use integrated genomic, transcriptomic, proteomic, and metabolomic approaches together with analytical profiling of carbohydrates to determine the composition of the multilayered cuticle in the red alga Chondrus crispus and assess its evolutionary conservation. The structural assembly reveals common features with the ECM of animals. The carbohydrate fraction includes a complex mixture of carrageenans and glycosaminoglycan-like compositions. A major von Willebrand factor A domain protein, Lamellae Cohesive Protein, plays a critical role in protein–protein interactions and binding to sulfated polysaccharides. We have further identified the major proteins of the algal cuticle, providing a framework for addressing the evolutionary origins of the cuticle and raising important questions regarding its role, particularly across the red algal life cycle marked by major structural differences in its ECM.